A Quantitative Trait Locus (LSq-1) on Mouse Chromosome 7 Is Linked to the Absence of Tissue Loss After Surgical Hindlimb Ischemia - Dokun, Ayotunde O. (2008)
BACKGROUND: Peripheral arterial disease (PAD) caused by occlusive atherosclerosis of the lower extremity has 2 major clinical manifestations. Critical limb ischemia is characterized by rest pain and/or tissue loss and has a ≥40% risk of death and major amputation. Intermittent claudication causes pain on walking, has no tissue loss, and has amputation plus mortality rates of 2% to 4% per year. Progression from claudication to limb ischemia is infrequent. Risk factors in most PAD patients overlap. Thus, we hypothesized that genetic variations may be linked to presence or absence of tissue loss in PAD. METHODS AND RESULTS: Hindlimb ischemia (murine model of PAD) was induced in C57BL/6, BALB/c, C57BL/6×BALB/c (F1), F1×BALB/c (N2), A/J, and C57BL/6J-Chr7(A/J)/NaJ chromosome substitution strains. Mice were monitored for perfusion recovery and tissue necrosis. Genome-wide scanning with polymorphic markers across the 19 murine autosomes was performed on the N2 mice. Greater tissue loss and poorer perfusion recovery occurred in BALB/c than in the C57BL/6 strain. Analysis of 105 N2 progeny identified a single quantitative trait locus on chromosome 7 that exhibited significant linkage to both tissue necrosis and extent of perfusion recovery. Using the appropriate chromosome substitution strain, we demonstrate that C57BL/6-derived chromosome 7 is required for tissue preservation. CONCLUSIONS: We have identified a quantitative trait locus on murine chromosome 7 (LSq-1) that is associated with the absence of tissue loss in a preclinical model of PAD and may be useful in identifying gene(s) that influence PAD in humans.